Crystal structure of (E)-2,2′,3,3′-tetrahydro-[1,1′-biindenylidene]-4,4′-diol, C18H16O2 - Hao Yuwei; Ren Zhilin; Bi Jingjing; Wang Haiyan; Chen Qiong (Zeitschrift für Kristallographie - New Crystal Structures)
C18H16O2, monoclinic, P21/c (no. 14), a = 5.6512(4) Å, b = 4.7795(3) Å, c = 22.9999(15) Å, β = 95.385(6)∘, V = 618.48(7) Å3, Z = 2, R gt(F) = 0.0545, wR ref(F 2) = 0.1712, T = 293(2) K.